Effects of Soil Moisture Deficit Levels at Irrigation time on Shoot and Root Growth Indices, Yield and Water Use Efficiency of Greenhouse Cucumber - A. shafaie; A. Karimi; R. Barzegar (Tulīd va Farāvarī-i Maḥṣūlāt-i Zirā̒ī va Bāghī, 2019)
The aim of this study was to evaluate the effect of different levels of soil moisture at irrigation time on root growth, yield and water use efficiency of greenhouse cucumber (Cucumis sativus L.), Yalda cultivar. The experiment was conducted in a randomized complete block design with six treatments and three replications in Isfahan Greenhouse Research Center in 2016. These experimental treatments included: field capacity (FC), 10% FC, 20% FC, 30% FC, 40% FC and 45% FC. Therefor, Irrigation was carried out after reducing the soil moisture to above values. In this experiment, plant height, leaf number, fresh weight of shoot, average leaf area, root length, root fresh weight, root dry weight, shoot to root ratio, fruit number, yield and water use efficiency were measured. The results showed that different levels of soil moisture at irrigation time had significant (p<0.05) effect on root growth, yield and water use efficiency of greenhouse cucumber. The results also indicated that root growth decreased with increasing soil moisture content. The highest root length, fresh and dry weight of the root were achieved with the treatment of 45% moisture content of the field capacity at irrigation time. The highest yield was obtained in FC and 10% FC treatments. The results showed that the best treatment was 10% FC  treatment due to highest water use efficiency (5.28 kg.m-3) and yield (12.3 kg.m-2).